Immune response to E7 protein of human papillomavirus type 16 anchored on the cell surface - Nemecková, Sárka; Stránská, Růzena; Subrtová, Jana; Kutinová, Luda; Otáhal, Pavel; Hainz, Petr; Maresová, Lucie; Sroller, Vojtech; Hamsíková, Eva; Vonka, Vladimír (Cancer immunology, immunotherapy, 2002)
To target the E7 protein of human papilloma virus 16 to the cell surface, a fusion gene was constructed. It encodes the signal peptide, part of the immunoglobulin (IgG)-like domain, the transmembrane anchor of vaccinia virus (VV) hemagglutinin (HA), and the complete E7-coding sequence. The fusion gene was expressed under the HA late promoter by a recombinant VV, designated VV-E7-HA. The E7-HA protein was displayed on the surface of cells infected with the recombinant virus and was more stable than unmodified E7. The biological properties of the VV-E7-HA virus were compared with those of a VV-E7 virus that expressed the unmodified E7 and with a VV expressing the Sig-E7-LAMP fusion protein. While the first two of these recombinants were based on VV strain Praha, the third was derived from the WR strain of VV. Infection of mice with the VV-E7-HA virus induced the formation of E7-specific antibodies with the predominance of the IgG2a isotype, whereas the other two viruses did not induce the formation of E7-specific antibodies. Unlike the other two viruses, VV-E7-HA did not induce a response of cytotoxic T lymphocytes or Th1 cells and did not protect mice against the growth of E7-expressing tumors. Thus, VV-E7-HA induced a differently polarized immune response to the E7 protein than the other two viruses.
Keywords: buněčná imunita; Papillomavirus E7 Proteins; Vaccinia virus; Hemagglutinins, Viral; Interleukin-4; Papillomavirus E7 - proteiny; experimentální nádory; myši inbrední C57BL; Vaccination; Antibodies, Viral; vakcinace; Immunity, Cellular; Mice; interleukin-4; Viral Vaccines; virové vakcíny; hemaglutininy virové; zvířata; králíci; Oncogene Proteins, Viral; Recombinant Fusion Proteins; Rabbits; Neoplasms, Experimental; rekombinantní fúzní proteiny; protilátky virové; myši; onkogenní proteiny virové; virus vakcinie; Mice, Inbred C57BL; Animals